2008
DOI: 10.1375/ajgc.18.2.182
|View full text |Cite
|
Sign up to set email alerts
|

Socially Prescribed and Self-Oriented Perfectionism as Predictors of Depressive Diagnosis in Preadolescents

Abstract: Perfectionism has been shown to be related to depressive symptomatology in both adult and child populations. However, there are no known studies of levels of socially prescribed (SPP) and self-oriented perfectionism (SOP) in nonclinical children versus those with a clinically diagnosed depressive disorder. Therefore, the aim of the current study was to examine SPP and SOP as predictors of depressive diagnoses in a sample of 10- to 11-year-old children. Seven hundred and eighty-six children (390 boys, 396 girls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 70 publications
5
43
1
2
Order By: Relevance
“…The magnitude of the association was also similar to the magnitude previously observed by researchers (e.g., Huggins et al, 2008). Further, consistent with most studies on perfectionism and depression, depressive symptoms shared a stronger concurrent relationship with SPP than SOP (Huggins et al, 2008;O'Connor et al, 2010;Kenney-Benson & Pomerantz, 2005;McCreary et al, 2004). Although both SOP and SPP were concurrently associated with depressive symptoms in Grade 7, the correlations between SOP and depressive symptoms was smaller than SPP (r = .11 for SOP and r = .29 for SPP).…”
Section: Cross-sectional Associationssupporting
confidence: 90%
See 4 more Smart Citations
“…The magnitude of the association was also similar to the magnitude previously observed by researchers (e.g., Huggins et al, 2008). Further, consistent with most studies on perfectionism and depression, depressive symptoms shared a stronger concurrent relationship with SPP than SOP (Huggins et al, 2008;O'Connor et al, 2010;Kenney-Benson & Pomerantz, 2005;McCreary et al, 2004). Although both SOP and SPP were concurrently associated with depressive symptoms in Grade 7, the correlations between SOP and depressive symptoms was smaller than SPP (r = .11 for SOP and r = .29 for SPP).…”
Section: Cross-sectional Associationssupporting
confidence: 90%
“…As well, SOP failed to predict depressive diagnostic status in another study (Huggins et al, 2008). Hence, while some authors found support for a link between SOP and depression in both childhood and adulthood, there is more consistent support for a link between SPP and depression in cross-sectional studies.…”
Section: Perfectionism and Depressionmentioning
confidence: 89%
See 3 more Smart Citations